The impact of osteoporotic fractures compared with other health conditions in older adults living in Virginia, United States. Issue 10 (October 2016) - Cunningham, T.; Martin, B.; DeShields, S.; Romero, C.
Abstract Summary This study compared length of stay, hospital costs, 30-day readmission, and mortality for patients admitted primarily for osteoporotic fractures to those admitted for five other common health conditions. The results indicated that osteoporotic fractures were associated with highest hospital charges and the second highest hospital stay after adjusting for confounders. Introduction This study aimed to compare the effect of osteoporotic fractures and other common hospitalized conditions in both men and women age 55 years and older on a large in-patient sample. Methods De-identified patient level and readmission and transfer data from the Virginia Health Information (VHI) system for 2008 through 2014 were merged. Logistic regression models were used to assess mortality and 30-day readmission, while generalized linear models were fitted to assess LOS and hospital charges. Results After adjustment for confounders, osteoporotic fractures had the second longest LOS (6.0 days, 95 % CI = 5.9–6.0) and the highest average total hospital charges (47, 386.0, 95 % CI = 46, 707.0–48, 074.0) compared to the other five common health problems. Conclusion Recognizing risk and susceptibility to osteoporotic fractures is an important motivator for individual behaviors that mitigate this disease. Furthermore, acknowledging the economic impact and disabling burden of osteoporotic fractures on society are compelling reasons to promote bone health as well as to prevent, diagnose, and manage osteoporosis.